2018
DOI: 10.1016/j.jisp.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Race and Alopecia Areata amongst US Women

Abstract: Few studies have examined the clinical epidemiology of alopecia areata (AA) in regard to patient race, and therefore, any disparities in incidence or prevalence of disease are largely unexplored. We sought to investigate potential racial disparities amongst two large cohorts of women. We conducted a cross-sectional analysis from the Nurses' Health Study (NHS) and Nurses' Health Study II (NHSII), wherein participants self-reported a diagnosis of AA. We determined odds ratios for AA by race in a multivariate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 13 publications
6
25
0
Order By: Relevance
“…7,8,12 Similarly to prior studies, Caucasians were the predominant race both groups, 14 but African Americans were disproportionately affected by AA. 14,15 Our findings are consistent with previous research indicating atopic dermatitis as the most common comorbidity among paediatric AA patients, but our calculated prevalence (17.4%) is lower than previous estimates of 28.6-34.4%. 7,8 Previous estimates used information from a national registry, which may be subject to bias due to the voluntary nature of registration likely dependent on provider, patient and/or parent preferences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…7,8,12 Similarly to prior studies, Caucasians were the predominant race both groups, 14 but African Americans were disproportionately affected by AA. 14,15 Our findings are consistent with previous research indicating atopic dermatitis as the most common comorbidity among paediatric AA patients, but our calculated prevalence (17.4%) is lower than previous estimates of 28.6-34.4%. 7,8 Previous estimates used information from a national registry, which may be subject to bias due to the voluntary nature of registration likely dependent on provider, patient and/or parent preferences.…”
Section: Discussionsupporting
confidence: 92%
“…Gender distribution is comparable to prior studies 7,8,12 . Similarly to prior studies, Caucasians were the predominant race both groups, 14 but African Americans were disproportionately affected by AA 14,15 …”
Section: Discussionsupporting
confidence: 74%
“…Few studies have investigated these conditions among Native American populations. A recent study of examining racial disparities for alopecia areas using the Nurses' Health Study also reported higher percentages of individuals with the condition among African Americans and Other races (American Indian, Asian, Native Hawaiian, or Pacific Islander) [51]. Some evidence has been found for a higher rate of primary biliary cirrhosis among British Columbia's First Nation's population [52], and one study identified a substantive overlap between RA and Sjögren's syndrome for an Oklahoma Native American population [53,54].…”
Section: Discussionmentioning
confidence: 98%
“…Alopecia areata (AA) is a T-cell mediated, autoimmune disorder which is mainly affecting anagen hair follicles and nails. Clinically, AA usually presents with localized circumscribed patches of nonscarring hair loss [1]. Alopecia totalis (AT) is a subtype of AA which is characterized by total hair loss on the face and scalp, whereas alopecia universalis (AU) is the other subtype of AA manifesting with generalized hair loss on hair-bearing regions of the body.…”
Section: Introductionmentioning
confidence: 99%